2010
DOI: 10.1159/000314343
|View full text |Cite
|
Sign up to set email alerts
|

Karyotyping in Melon (Cucumis melo L.) by Cross-Species Fosmid Fluorescence in situ Hybridization

Abstract: Chromosome identification is critical for cytogenetic research and will accelerate studies on genetic variation and breeding, especially for those species with relatively little sequence information. So far, no reliable cytological landmarks have been developed to distinguish individual chromosomes in melon. In this study, using FISH (fluorescence in situ hybridization) combined with comparative genome information, we selected 21 cucumber fosmids anchored by SSR markers as chromosome-specific cytological marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 63 publications
(47 reference statements)
5
23
0
1
Order By: Relevance
“…Consist with the previous results [Liu et al, 2010], the C. melo genome contained one 5S rDNA site (green) on chromosome 12 and two 45S rDNA sites (red) on chromosomes 4 and 10 ( Fig. 1 a2, a4).…”
Section: Chromosomal Distribution Of 5s and 45s Rdna In Several Diplosupporting
confidence: 89%
See 3 more Smart Citations
“…Consist with the previous results [Liu et al, 2010], the C. melo genome contained one 5S rDNA site (green) on chromosome 12 and two 45S rDNA sites (red) on chromosomes 4 and 10 ( Fig. 1 a2, a4).…”
Section: Chromosomal Distribution Of 5s and 45s Rdna In Several Diplosupporting
confidence: 89%
“…Previous studies showed that C. melo had one 5S rDNA locus on chromosome 12 and two 45S rDNA loci on chromosomes 4 and 10, and C. hystrix had three 45S loci on chromosomes 8, 10, and 12, respectively [Liu et al, 2010;Yang et al, 2014]. To identify chromosomes with rDNA loci in C. melo and C. hystrix , 2 oligo libraries were synthesized suitable for chromosome painting.…”
Section: Synthesis and Hybridization Of Oligo Painting Probes In Sevementioning
confidence: 99%
See 2 more Smart Citations
“…In Cucumis, studies involving molecular cytogenetics were mainly focused on important cultivated crops (e.g., cucumbers, melons) (Chen et al 1998;Han et al 2008;Liu et al 2010). Few relevant studies have been reported concerning the genome organization and chromosomal structure of wild species, except for some concerning chromosome morphology and karyotype (Chen et al 1999;Zhao et al 2011;Yagi et al 2014Yagi et al , 2015.…”
Section: Introductionmentioning
confidence: 99%